Literatūrinė Kauno regiono savimonė Literary self-consciousness of Kaunas region - Žakevičienė, Indrė (editor) (Vytautas Magnus University, 2011)
The articles of the book reveal the results of the research made on literary self-consciousness of Kaunas region, reflecting specific transformations of the places written from the 19th century till nowadays. To the problems stipulated by the concepts of the region, place and space are being analysed from the point of view of naratology, cultural geography and bioregionalism. The creative works written during the period from the 19th century till the beginning of the 21th century are being analysed as well, including the texts of Lithuanian literature for children.